2020
DOI: 10.1371/journal.pone.0228899
|View full text |Cite
|
Sign up to set email alerts
|

Microbial resolution of whole genome shotgun and 16S amplicon metagenomic sequencing using publicly available NEON data

Abstract: Microorganisms are ubiquitous in the biosphere, playing a crucial role in both biogeochemistry of the planet and human health. However, identifying these microorganisms and defining their function are challenging. Widely used approaches in comparative metagenomics, 16S amplicon sequencing and whole genome shotgun sequencing (WGS), have provided access to DNA sequencing analysis to identify microorganisms and evaluate diversity and abundance in various environments. However, advances in parallel high-throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 76 publications
9
99
0
Order By: Relevance
“…Stool samples were collected according to standard operating procedures [18] and were analysed using next-generation sequencing (NGS) for assessment of the faecal microbial composition [24]. Total DNA was extracted from faecal samples using a QIAmp DNA stool mini kit according to the manufacturer's instructions (Qiagen, Hilden, Germany), coupled with an initial bead-beating step.…”
Section: Next-generation Sequencing For Determination Of the Microbiomentioning
confidence: 99%
“…Stool samples were collected according to standard operating procedures [18] and were analysed using next-generation sequencing (NGS) for assessment of the faecal microbial composition [24]. Total DNA was extracted from faecal samples using a QIAmp DNA stool mini kit according to the manufacturer's instructions (Qiagen, Hilden, Germany), coupled with an initial bead-beating step.…”
Section: Next-generation Sequencing For Determination Of the Microbiomentioning
confidence: 99%
“…Therefore, there is a probability that some of these methodologies might have missed to disclose certain penile bacteria. Thus, an important consideration for future studies is inclusion of appropriate controls and use of more accurate metagenomic approaches like whole-genome sequencing (WGS) methods that have enhanced microbial resolution and allowed detection of putative functional gene composition of microbiota (119).…”
Section: Gaps and Challenges In The Current Literature And Future Promentioning
confidence: 99%
“…Associations between the microbial profile and cancer have so far been based mainly on the sequencing of bacterial 16S ribosomal RNA (rRNA) genes. It has been shown that significant differences in the analysis of whole bacterial genomes improve the characterization of microbial communities, even at the subtype/strain level ( Ranjan et al, 2016 ; Brumfield et al, 2020 ).…”
Section: Microbiomementioning
confidence: 99%